Existence of Solutions of Antiperiodic Boundary Value Problems for a Non Linear Third Order Impulsive Integro Dynamic System on Time Scales - Arunkumar, D.; Sivabalan, M.; Sathiyanathan, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper explores the existence of solutions for the system of impulsive integrodifferential equation with anti-periodic boundary value problems on time scales. Some sufficient conditions for the existence of solutions are established by using Schauder’s fixed point theorem and Schaefer fixed point theorem.